Could orchids indicate truffle habitats? : mycorrhizal association between orchids and truffles - Ouanphanivanh, Noémi (Acta Biologica Szegediensis, 2008)
Each member of the Orchidaceae family is in symbiosis with fungi. It has been explicitly stated that some forest orchid species are mycorrhizated by ectomycorrhizal fungi connected to trees, instead of classic orchid symbionts. These orchids supply their required nutrients via fungi. Our investigation aimed at analysing the data of a computerized database on hypogeous fungi. This database contains the data on hypogeous fungi gathered in the Carpathian basin, and also the coenological relevés made in their quadrat. We have found 16 hypogeous fungal genera with close presence of orchids (genus Cephalanthera and genus Epipactis), that is l3 % of all relevés. In case of two fungal genera (Tuber and Hymenogaster) the orchid co-occurence proved to be more frequent than average, so these fungal taxons were supposed to be in mycorrhizal connection with the orchids. Tuber maculatum, and Tuberexcavatum species were identified based on nrITS sequence analysis of three orchid individuals. Tuber maculatumhas been firstly identified from orchid root in this case.